Figurative Language in Pananaroon: A Linguistic and Cultural Analysis of Meranaw Proverbs - Alican Mendez Pandapatan (Journal of Social, Culture, and Language, 2025)
The study delves into the figurative language of Pananaroon (Meranaw Proverbs) examines their linguistic structures as well as cultural significance. This grounded in a deep-rooted oral tradition which uses aa qualitative naturalistic approach. The data gathered from key informants across three towns in Lanao del Sur, Bakolod-Kalawi, Maguing, and Masiu. One-on-one discussions and focus group discussions are conducted. The results indicate that the literal and the connotative meanings reveal essential values such as humility, wisdom, honor, and emotional strength. Semantically and semiotically, the analyses reveal that paananaroon are rich with metaphors, personification, symbolism, hyperbole, irony, and imagery. Each pananaroon reflects deeply held Meranaw values such as wisdom, humility, honor, emotional strength, and community harmony. The findings show that pananaroon not only serve as poetic expressions but also transmit moral teachings across contexts such as courtship, patriotism, leadership, and pride. These cultural contexts act as vessels of knowledge, sustaining Meranaw identity and philosophy in the face of challenges. The study underscores the essence of preserving oral traditions and recommends to integrate them into cultural and educational programs to strengthen linguistic appreciation and cultural heritage among younger generations.